Common Fixed Point Theorems in Menger Probabilistic Quasimetric Spaces. (1st June 2009) - Sedghi, Shaban; Žikić-Došenović, Tatjana; Shobe, Nabi
Abstract : We consider complete Menger probabilistic quasimetric space and prove common fixed point theorems for weakly compatible maps in this space.